Thioxanthone-ethyl anthracene - Balta, Demet Karaca; Arsu, Nergis (ELSEVIER SCIENCE SA, 2013)
Thioxanthone-2-ethyl anthracene (TX-EA) was synthesized and characterized as part of our continuing interest in synthesizing polyaromatic initiators which have good absorption properties in the UV and visible region of the electromagnetic spectrum (epsilon(329): 28,746 M-1 cm(-1), epsilon(430):5028 M-1 cm(-1)). The fluorescence quantum yield was calculated as 0.025 which is slightly lower than that of the parent thioxanthone compound (phi(f): 0.07). The triplet lifetime was found to be 3.9 mu s from laser flash photolysis studies. The initiating efficiency of TX-EA was found to be highly efficient for mono and multifunctional acrylates from the results obtained from the solution polymerization and photo-DSC in the presence and absence of MDEA in air atmosphere. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Photopolymerization; Photoinitiator; Thioxanthone; FREE-RADICAL POLYMERIZATION; DOUBLE CLICK REACTIONS; CHAIN THIOXANTHONE; FLUORESCENCE; BENZOPHENONE; CHEMISTRY; INITIATOR; AMINE